A theological reflection of bivocational pastoral ministry: a personal reflective account of a decade of bivocational ministry practice experience - Samushonga, Hartness M. (Practical theology, 2019)
Bivocational Ministry (BM) practice is not a new phenomenon. Ministry practitioners are increasingly taking on the option of serving in ministry at the same time as having another vocation outside of ministry. However, in addition to a dearth of research that focuses on BM; the scarcity of reflective academic discourse on BM is apparent. This paper, nonetheless, offers a valuable contribution to this area of Practical Theology, which deserves attention. It draws from 10 years of consistent BM practice through a reflective methodology. This reflection explores various aspects of BM and engages questions of the authenticity and the efficacy of BM through theory, which include Scripture and research. This paper thus provides a viable foundation for further academic discourse on the notion of BM.